Reconquista Ibérica: an ocean of ink between historiography and the Primera Cronica General de España: No presente artigo buscamos compreender como o conceito de Reconquista foi forjado dentro da historiografia. Tendo como alicerce os principais medievalistas ibéricos e não peninsulares que abordaram esta temática. Para assim buscarmos pensar como a Reconquista é interpretada na historiografia até a contemporaneidade. Contrapondo a historiografia buscamos entender como este conceito aparece dentro da fonte Primera Crónica General de España. Para determinada compreensão selecionamos duas batalhas entre cristão e muçulmanos, a primeira é Covadonga em 711, a segunda La Navas de Tolosa 1212. A escolha destes conflitos foi devido ao fato que são leituras bélicas em distintos momentos da Idade Média Ibérica. Neste sentido, o nosso objetivo é entender se existe uma mentalidade bélica no mundo Ibérico que visava reconquistar o território ibérico. Palavras-Chave: Reconquista, Historiografia, Primera Crónica General de España. (Revista de História da UEG (REVHIST), 2024)
In this article, we seek to understand how the concept of Reconquest was forged within historiography. Based on the main Iberian and non-Iberian medievalists who addressed this theme. In order to try to think about how the Reconquest is interpreted in historiography up to the present day. Contrasting the historiography, we seek to understand how this concept appears within the Primera Crónica General de España source. For a certain understanding, we selected two battles between Christians and Muslims; the first is Covadonga in 711, the second La Navas de Tolosa in 1212. The choice of these conflicts was because they are warlike readings in different moments of the Iberian Middle Ages. In this sense, our objective is to understand if there is a warlike mentality in the Iberian world that aimed to reconquer the Iberian territory.Keywords: Reconquista. Historiography. Primera Crónica General de España.